2007
DOI: 10.1074/jbc.m609916200
|View full text |Cite
|
Sign up to set email alerts
|

A Periplasmic Iron-binding Protein Contributes toward Inward Copper Supply

Abstract: Periplasmic substrate binding proteins are known for iron, zinc, manganese, nickel, and molybdenum but not copper. Synechocystis PCC 6803 requires copper for thylakoid-localized plastocyanin and cytochrome oxidase. Here we show that mutants deficient in a periplasmic substrate binding protein FutA2 have low cytochrome oxidase activity and produce cytochrome c 6 when grown under copper conditions (150 nM) in which wild-type cells use plastocyanin rather than cytochrome c 6 . Anaerobic separation of extracts by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 47 publications
2
51
2
Order By: Relevance
“…Upon entering the periplasm FutA2 binds Fe(III), generating the chemical gradient that facilitates the influx of Fe. This is consistent with the suggested role for FutA2 in metal partitioning in the periplasm (Waldron et al, 2007). On the basis of our findings (Figures 2 and 3), FutA2 is a major factor in determining iron reduction and subsequent transport.…”
Section: Coordinated Transporter Activity C Kranzler Et Alsupporting
confidence: 92%
“…Upon entering the periplasm FutA2 binds Fe(III), generating the chemical gradient that facilitates the influx of Fe. This is consistent with the suggested role for FutA2 in metal partitioning in the periplasm (Waldron et al, 2007). On the basis of our findings (Figures 2 and 3), FutA2 is a major factor in determining iron reduction and subsequent transport.…”
Section: Coordinated Transporter Activity C Kranzler Et Alsupporting
confidence: 92%
“…The binding of ferrous iron by FutA2 in this investigation contrasts the results of the work done by Waldron et al, which concluded that FutA2 binds ferric iron in vitro (9). The data presented here represent the first test of both ferric and ferrous iron binding to FutA1 or FutA2.…”
contrasting
confidence: 82%
“…FutA2 Purification-FutA2 was purified and refolded from inclusion bodies as previously described (9). Approximately 2 g of cells were thawed in 35 ml of inclusion body buffer (50 mM HEPES, pH 7.5, 500 mM NaCl, 5 mM MgCl 2 , 1% Triton X-100) with 10 mM ␤-mercaptoethanol, DNase I, and lysozyme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Another protein that have been implicated in copper transport is FutA2, which electrophoretic mobility changes in the presence of the Cu + -chelator, and a mutant in the corresponding gene is impaired in copper import and has reduced levels of intracellular copper proteins. 8 CtaA and PacS are thought to transport reduced copper, although copper is present in the growth medium in it oxidized state, pointing to the existence of an unidentified copper reductase in cyanobacteria.…”
mentioning
confidence: 99%